INNOVATIVE APPROACHES TO SUSTAINABLE DEVELOPMENT: ECOLOGICAL STARTUPS AND GREEN TECHNOLOGIES - Тетяна Кулініч; Віталій Нагорний; Ольга Рубан (Економіка та суспільство)
In the modern world, the issue of sustainable development is becoming increasingly relevant, as it is driven not only by global environmental challenges but also by new economic realities that focus on the transition from a traditional economy to a sustainable one. Such an economy involves resource reuse, waste minimization, and greening of production processes. As a result of the increasing relevance of these needs over the past decade, the development of economic systems today is focused on ecological entrepreneurial initiatives (startups) and the green technologies developed within them. These technologies are capable of ensuring sustainability both for society and for business. Thus, the article aims to study innovative approaches to sustainable development implemented through ecological startups and green technologies. These technologies can reduce carbon emissions, promote renewable energy use, enhance energy efficiency, minimize risks, and adapt economic processes to new climate conditions.